A Look at the Crimean Declaration of Independence through the Lens of International Law - Odityo, Hikmah Bima (Yustisia, 2023)
It has been argued that the government officials in Kyiv are attempting to retake Crimea and restore sovereignty over the region. It is appealing since the issue of Crimea remains unsettled. In 2014, the Crimean parliament promulgated the Declaration of Independence and imminently voted for a referendum to accede to the Russian Federation. Similar cases also occurred in Donetsk, Luhansk, Zaporizhzhia, and Kherson in 2022. This article will examine Crimean rights to self-determination to assess whether such acts comply with international law. Furthermore, this article will mainly focus on Crimean’s declaration of independence and its referendum to determine the status and impact of such acts. It can be seen that Crimea, as de facto is part of Russia. However, as de jure, the territory might belong to Ukraine. Considering that they have voted for independence, both the Crimean people and Ukraine authorities can further negotiate a new legal status to accommodate their rights.